A contribuição do Behaviorismo Radical para a formação de professores- Uma análise a partir das dissertações e teses no período de 1970 a 2002 - Rodrigues, Maria Ester (2005)
This research aims at analyzing the contribution of Radical Behaviorism on formation, taking into account thesis and dissertations from 1970 to 2002, which means the thirty-two years of existence of the Brazilian masters strictu sensus course. Due to the lack of records and descriptive studies concerning the analysis of behavior and education in Brazil, as well as the widespread misunderstandings of Behavior Analysis/ Radical Behaviorism (BA/RB) on courses and books devoted to formation, the present research is justified. There was an evaluation of 10.174 abstracts concerning thesis and dissertations presented to Brazilian Post-Graduation strictu sensu Programs, from a total of thirteen institutions where there was the chance to find these works on BA/RB. Observing this kind of work, 282 researches corresponding to 2.77% of published thesis and dissertations from the analyzed programs were found. Seventeen of them were specifically referred to formation (0.16%). From the 282 ones, 265 abstracts were read since they were focused on general education, and also some aspects as place, responsible institution for the research, advisors and institutions productivity. The seventeen researches remaining are specifically about formation, which were analyzed according to the categories built from suggestions supplied by, basically, three authors (Bijou, 1970; Zanotto, 1997 and Gioia, 2001), in agreement with Skinner s proposal. Besides analyzing the general features, aspects about philosophy, basic concepts and researches of behavior analysis were also highlighted as well as teaching itself. Among these results, we found out that authors justify their researches since there is a need to overcome this lack on formation regarding formation and educational role. The researches were carried out through an experimental and mixed outline, but the number of teachers and students involved in the study may be considered significant (nearly 85 teachers and 1.800 students), as a consequence of the small number of researches found along this thirty-two year period of analysis. The authors dedicated themselves mainly to the first years from the elementary school, followed by kinder garden/children s education and special education, but the works focused on second part from elementary school, high school and college courses were less significant. It is important to stand out that the most important content was teaching, especially the teacher's autonomy on planning and executing their teaching activities, regarding to whom he teaches also observing the students ' first repertory; what he teaches or the establishment of his goals; how he teaches regarding some of its subdivisions, as the correct and effective uses of supplements; promotion and maintenance of behavior generalization after its installation; respect to the student's pace, and individualization of teaching; observation and holding of records about the students' behavior; the ranking of contents and their difficulties on suggesting or using strategies and teaching procedures. The emphasis on how to teach as well as on teaching the teacher how to teach appears to be a great contribution from the analyzed researches, but this can not be regarded as a recipe . Other points are suggested from these results, as an important aspect to think about; they also need more attention from the behavior analysts. An example can be the philosophical/conceptual teaching aspects, knowledge conceptions, teaching-learning, among others. The results also suggest the need of historical studies questioning the relationship between BA/RB and technicism which was declared by Brazilian education literature, once this research present information that is opposite to this assertion (reduced utilization of educational technology). These answers also suggested that community should reflect on insertion of BA/RB practices on education and on a closer contact with teachers, in order to give proposals to overcome those misunderstandings regarding the approach and the rejection to BA/RB received in the educational class